Molecular characterization of Neoechinorhynchus cylindratus Van Cleave, 1913 (Acanthocephala: Neoechinorhynchidae), a parasite of the largemouth bass (Micropterus salmoides) in northern Mexico. (2020) - García-Varela, M.; Pinacho-Pinacho, C.D.
Abstract: Members of the genus Neoechinorhynchus Stiles & Hassall, 1905 are endoparasites of freshwater fishes, brackish water fishes, and freshwater turtles distributed worldwide. In North America, 33 species have been described. One of the most widely distributed species in the eastern United States and Canada is Neoechinorhynchus (Neoechinorhynchus) cylindratus, a common acanthocephalan that infects centrarchid fishes. In the current study, adult specimens of N. (N) cylindratus were collected from largemouth bass ( Micropterus salmoides ) from the Purificación River in northern Mexico. In the same freshwater system, two additional congeneric species ( Neoechinorhynchus (Neoechinorhynchus) emyditoides and Neoechinorhynchus (Neoechinorhynchus) panucensis ) were collected and analysed. Sequences of the large subunit, internal transcribed spacers ITS1 and ITS2, 5.8S from nuclear DNA, and sequences of the cytochrome c oxidase subunit I ( cox 1) from mitochondrial DNA were generated and aligned with other sequences obtained from GenBank. Maximum likelihood and Bayesian inference analyses inferred for each dataset showed that N. (N) panucensis, N. (N) emyditoides and N. (N) cylindratus were nested within several clades, indicating that these species do not share a common ancestor. Our phylogenies also revealed that the genus Neoechinorhynchus is paraphyletic, requiring further taxonomic revision using phylogenetic systematics and re-examination of morphological and ecological data. The presence of several N. (N) cylindratus adults in northern Mexico allowed us to typify this species for the first time using a combination of morphological and molecular characteristics. The current record shows a wide distribution range of N. (N) cylindratus across Canada, the United States and Mexico in the Nearctic region.